The White Book of the Catalan Transborder Eurodistrict: project creation and territorial restructuring - Castañer, Margarida; Feliu, Jaume; Gutiérrez, Obdúlia (Documents d’Anàlisi Geogràfica, 2011)
We present the process of elaboration, methodology, reflections and conclusions of the White Book of Catalan Transborder Eurodistrict, elaborated by the Mission Opérationnelle Transfrontalière (MOT) and the University of Girona (UdG). The main purpose of this study is to help the definition and the emergency of a transborder territorial project based on the territorial reality shared between the department of the Oriental Pyrenees and the province of Girona. The content of White Book is divided into three parts: a complete transborder diagnosis, the analysis of the challenges of this territory and the options of governance of the transborder territory. After portraying the territorial context, the methodology and the conclusions of the study, a brief review of which the state of the process at the present time is made.